FEMINISME DALAM NOVEL BIBIR MERAH KARYA ACHMAD MUNIF - yani, inda (Buana Bastra, 2014)
Abstract Bibir Merah novel is very interesting when it is studied on the behavior, attitudes, and the language expression in the figures. The foundation of the theory used in this study is the theory of feminism. The method used in this research is descriptive qualitative. Data collected in the form of words, phrases, sentences that mention the dual role of women in the Bibir Merah novel by Achmad Munif. Data collection is done by reading the source data. The result of this research is the behavior of the characters in the Bibir Merah novel by Ahmad Munif as the reaction of Rumanti to the treatment of her invironment. The attitude of the characters in the Bibir Merah novel by Ahmad Munif is an act of Rumanti based on her belief over the plight of her life. The language expression in the Bibir Merah novel by Achmad Munif is the language expression of a gentle character. She pulled out a woman 's inner beauty generally owned by a woman. Keywords: feminism, behaviors, attitudes, and language expression.